Parent Provision of Choice Is a Key Component of Autonomy Support in Predicting Child Executive Function Skills - Castelo, Romulus J.; Meuwissen, Alyssa S.; Distefano, Rebecca; McClelland, Megan M.; Galinsky, Ellen; Zelazo, Philip David; Carlson, Stephanie M. (Frontiers in Psychology, 2022)
Although previous work has linked parent autonomy support to the development of children’s executive function (EF) skills, the role of specific autonomy-supportive behaviors has not been thoroughly investigated. We compiled data from four preschool-age samples in the midwestern United States (N = 366; M age = 44.26 months; 72% non-Hispanic White, 19% Black/African American, 5% Multiracial) to examine three relevant autonomy-supportive behaviors (supporting competence, positive verbalizations, and offering choice) and their associations with child EF. We coded parent autonomy-supportive behaviors from a 10-minute interaction between parent and child dyads working on challenging jigsaw puzzles together. Children completed a battery of EF Overall, child EF was most consistently correlated with the offering choice subscale. Additionally, only the offering choice subscale predicted child EF while controlling for the other autonomy support subscales and child age. These results suggest that parent provision of choice is an especially relevant aspect of autonomy-supportive parenting and may be important to the development of EF in early childhood. Future research should directly measure children’s experience with choice and how it relates to emerging EF.